Avian pox in a turkey vulture (Cathartes aura) from northern Chile - Mora-Carreño, Mauricio; Guerra-Correa, Carlos; Moroni, Manuel; Paredes, Enrique (Austral Journal of Veterinary Sciences, 2019)
A debilitated turkey vulture (Cathartes aura), showing prominent nodular masses in its head, was found in Antofagasta, Chile. Histopathological examination revealed the presence of epidermal hyperplasia and hypertrophy with typical eosinophilic intracytoplasmatic inclusion bodies in epithelial cells. Accordingly, a diagnosis of avian pox was established, corresponding to the first known occurrence of the disease in the southern hemisphere.